PDOL-Based Solid Electrolyte Toward Practical Application: Opportunities and Challenges - Yang, Hua; Jing, Maoxiang; Wang, Li; Xu, Hong; Yan, Xiaohong; He, Xiangming (Nano-Micro Letters, 2024)
Polymer solid-state lithium batteries (SSLB) are regarded as a promising energy storage technology to meet growing demand due to their high energy density and safety. Ion conductivity, interface stability and battery assembly process are still the main challenges to hurdle the commercialization of SSLB. As the main component of SSLB, poly(1,3-dioxolane) (PDOL)-based solid polymer electrolytes polymerized in-situ are becoming a promising candidate solid electrolyte, for their high ion conductivity at room temperature, good battery electrochemical performances, and simple assembly process. This review analyzes opportunities and challenges of PDOL electrolytes toward practical application for polymer SSLB. The focuses include exploring the polymerization mechanism of DOL, the performance of PDOL composite electrolytes, and the application of PDOL. Furthermore, we provide a perspective on future research directions that need to be emphasized for commercialization of PDOL-based electrolytes in SSLB. The exploration of these schemes facilitates a comprehensive and profound understanding of PDOL-based polymer electrolyte and provides new research ideas to boost them toward practical application in solid-state batteries. Highlights: 1 The poly(1,3-dioxolane) (PDOL) electrolyte demonstrates promising potential for practical application due to its advantages in in-situ polymerization process, high ionic conductivity, and long cycle life. 2 This review focuses on the polymerization mechanism, composite innovation, and application of PDOL electrolytes. 3 This review provides a comprehensive summary of the challenges associated with the PDOL electrolyte and makes forward-looking recommendations.